2015
DOI: 10.1002/cctc.201501083
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of and Mechanistic Considerations for the Enantioselective Dihydroxylation of Styrene Catalyzed by Osmate‐Laccase‐Poly(2‐Methyloxazoline) in Organic Solvents

Abstract: The Sharpless dihydroxylation of styrene with the artificial metalloenzyme osmate‐laccase‐poly(2‐methyloxazoline) was investigated to find reaction conditions that allow this unique catalyst to reveal its full potential. After changing the co‐oxidizing agent to tert‐butyl hydroperoxide and optimizing the osmate/enzyme ratio, the turnover frequency and the turnover number could be increased by an order of magnitude, showing that the catalyst can compete with classical organometallic catalysts. Varying the metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
0
6
1
Order By: Relevance
“…The resulting acylated LYS′s are not soluble in organic solvents in contrast to the respective formerly reported poly(2‐oxazoline) (POx)‐conjugates, but form stable suspensions in various organic solvents such as toluene and chloroform (Figure ).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…The resulting acylated LYS′s are not soluble in organic solvents in contrast to the respective formerly reported poly(2‐oxazoline) (POx)‐conjugates, but form stable suspensions in various organic solvents such as toluene and chloroform (Figure ).…”
Section: Resultsmentioning
confidence: 92%
“…The reaction was carried out with 0.03 μmol mL −1 protein conjugate, 0.03 μmol mL −1 K 2 OsO 2 (OH) 4 , 110 μmol mL −1 t BuOOH and 100 μmol mL −1 styrene. The reaction times were adjusted to previously determined surviving times of a respective Os‐laccase‐PMOx under the used conditions and temperatures, being 7 d at 0 °C, 72 h at 20 °C, and 24 h at 40 °C . The TOF is defined as μmol product per μmol protein per hour.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Goal of the present study was to explore the potential of poly(2‐ethyloxazoline) (PEtOx) as matrix material for the activation of enzymes in electrospun nanofibers in organic solvents. We choose this polymer, because it was found enzyme friendly in solution, in amphiphilic polymer conetworks based on PEtOx, and even as enzyme–polymer conjugates to make the proteins organosoluble (Konieczny et al, ), reactive (Konieczny et al, ), and even applicable as ligands for organo‐metal catalysis (Konieczny et al, ; Leurs et al, ). Al‐Shehri et al () have reported that enzymes can be electrospun from an aqueous solution of commercial PEtOx ( M w = 500,000 g/mol).…”
Section: Resultsmentioning
confidence: 99%